The Determinants of Indonesian Textile’s and Clothing Export to the Five Countries of Export Destination - Faizal Irvansyah; Hermanto Siregar; Tanti Novianti (ETIKONOMI, 2020)
Indonesian textile and clothing products (TPT) is the second-largest export product after oil palm product. There are five biggest export destination countries, that is the United States, Japan, South Korea, and Turkey. This study aims to analyze the factors that affect TPT exports to the five biggest export destination countries. The factors that affect TPT exports examined by using time series and panel data analysis. Using panel data analysis finds that GDP per capita of the destination country, the exchange rate of the Rupiah, the price of textiles in the destination country, and import tariffs stipulate in the destination country affect TPT exports. Then, using time series analysis finds that GDP per capita and import tariffs affected TPT export to the United States, China, and Turkey. Meanwhile, the factors influencing Indonesian textile exports to Japan and South Korea are textile prices, rupiah exchange rates, and import tariffs.JEL Classification: F14, F43How to Cite:Irvansyah, F., Siregar, H., & Novianti, T. (2020). The Determinants of Indonesian Textile’s and Clothing Export to the Five Countries of Export Destination. Etikonomi: Jurnal Ekonomi, 19(1), 19 – 30. https://doi.org/10.15408/etk.v19i1.14845.